PENYEBARAN DAN PERMUDAAN JENIS-JENIS BURSERACEAE DI HUTAN DIPTEROCARPACEAE, WANARISET, KALIMANTAN TIMUR - SITI SUNARTI (BERITA BIOLOGI, 1987)
SITI SUNARTI. 1987. Distribution and regeneration of Burseraceae in a lowland dipterocarp forest at Wanaiiset, East Kalimantan. Berita Biologi,3 (7) : 333 - 341. A study on distribution and regeneration of Burseraceae was carried out in a 5.25 ha plot of a lowland dipterocarp forest in East Kalimantan. A total of 94 mature trees, 699 saplings, and 3511 seedlings were recorded. Mapping and pattern analysis (using Morisita method) indicate that, adult and juvenile trees have clustered distributional patterns. Positive corelations between regeneration and gap size were observed in saplings and seedlings of Dacryodes and in sjplings of Santiria spp. No such corelation was noted in Canadian spp.